A CROSS-SECTIONAL STUDY ON THE PREVALENCE OF DEPRESSION AND ITS IMPACT ON THE QUALITY OF LIFE IN PATIENTS WITH OCD. - Dr. Farheen fatma; Dr .Dhruv (Student's Journal of Health Research, 2023)
Background: A complex and challenging mental health condition due to which millions of people are affected worldwide is depression. It extends well beyond mere sadness or occasional spells of low mood. Instead, depression is a persistent and pervasive sense of despair, hopelessness, and emotional pain that can significantly disrupt a person's life. Objective: Anxiety disorders can significantly diminish a person's quality of life (QOL), as this appears to be especially pertinent in the case of individuals dealing with obsessive-compulsive disorder (OCD). This research delves into how obsessions, compulsions, and the presence of depression uniquely influence the life quality of individuals living with OCD. Method: A group of eighty-six individuals who had been diagnosed with OCD based on "DSM-IV criteria" and were dealing with significant compulsions and obsessions participated in this study. The completed assessments related to their quality of life, the intensity of their obsessive-compulsive symptoms, and the severity of their depression. Results: The severity of obsessive-compulsive disorders was found to significantly predict patients with depression, a significant relationship between obsession severity and sickness intrusiveness was also found (t = 2.09, P<0.05), higher obsession severity being associated with higher illness intrusiveness. Conclusion: Considering the importance of these symptoms, there is a clear need for OCD sufferers to get therapies that focus on obsessions and related depression symptoms. It's crucial to remember that these results should be verified in prospective cohort research. The current cross-sectional approach does not establish the temporal order or causal links between obsessions, depression, and quality of life (QOL), but it does allow for the analysis of the association between obsession depression, and QOL. Consequently, a longitudinal study is necessary to comprehend the chronological context of these components